AB0180 Hypovitaminosis d predicts more aggressive evolution and lower response to treatment in early rheumatoid arthritis after 12 months of follow-up. (23rd January 2014) - Gerardi, M. C.; Barchetta, I.; Ceccarelli, F.; Frisenda, S.; Iannuccelli, C.; Cavallo, G.; Valesini, G.; Di Franco, M.
Abstract : Background: It has been suggested that thevitamin D active form (1, 25(OH)2D3 ) has immunoregulatory activities, regulating both the innate and adaptive immune responses. Recently, vitamin D has been studied as potential player in the pathogenesis of Rheumatoid Arthritis (RA). Several studies have investigated the effects of vitamin D on pathogenesis and disease activity in RA, showing a negative association between serum vitamin D levels and RA activity[i]. Objectives: Aim of this study was to test the hypothesis of an association between serum vitamin D levels and the disease activity evaluated with clinimetric, biochemical and ultrasound (US) parameters after a follow-up of 12 months in early RA patients. Methods: For this purpose, we recruited 37 consecutive patients affected by early RA and naïve for treatment among patients referring to the Early Arthritis Clinic of the Rheumatology Unit. Hypovitaminosis D was diagnosed for 25(OH) vitamin D value < 20 ng/ml. Serum C-reactive protein (CRP), Erytrocytes Sedimentation Ratio (ESR), Reumathoid Factor (RF) and anti-citrullinated peptide antibody (ACPA) levels were also measured in our study population. Swollen and tender joint counts, Disease Activity Score 28 and 44 joints assessment (DAS28 and DAS44) scores, Simplified Disease Activity Index (SDAI) and the Clinical Disease Activity Index (CDAI) were assessed at baseline and after 12 months from the diagnosis of RA. All patients underwent US assessment for synovitis and powerDoppler evaluation. Results: At baselinepatients with low levels of vitamin D did not show any significant difference compared to patients with normal levels of vitamin D as for clinimetric, serological and US parameters. After a 12 months follow-up patients with sufficient 25(OH)D levels at baseline had a significant lower disease's activity evaluated by DAS28, DAS44, CDAI and SDAI (p<0.001 for all indexes) and a higher prevalence of remission compared to the group with hypovitaminosis D (68% vs 16%, respectively; p<0.001) according to EULAR criteria and to DAS44, CDAI and SDAI scores (p<0.001 for all indexes). Accordingly, normal vitamin D levels was also associated with higher percentage of responders to RA treatment (EULAR criteria) compared with vitamin D insufficiency (100% vs 75%, p<0.001). At the follow-up of 12 months, US synovitis score increased in 42.8% of patients with hypovitaminosis D whereas it worsened only in 12% of patients with normal serum 25(OH) vitamin D at baseline (p<0.001). Conclusions: In the present study, subjects with early RA and baseline normal vitamin D levels showed both a greater reduction of disease activity and higher prevalence of response to treatment and remission compared to patients with hypovitaminosis D, after 12 months of follow-up. Our results provide further support to the immunomodulatory role of vitamin D in inflammatory arthritis and indicate that baseline hypovitaminosis D may predict a more aggressive evolution of the disease. Thus, evaluation of vitamin D serum levels and its possible supplementation should become part of the clinical practice, especially in patients naïve to treatment. References: Song GG, Bae SC, Lee YH. Association between vitamin D intake and the risk of rheumatoid arthritis: a meta-analysis. Clin Rheumatol (2012) 31:1733–1739. Disclosure of Interest: None Declared